Penerapan Teknologi Gas Oven Rotary Untuk Mendukung Optimasi Produksi Pada UMKM D’Lor Bakery - Harjianto; Lestari, Sutami Dwi; Anam, Muhamad Khoirul; Hasyim As’ari; Qiram, Ikhwanul (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) have an essential role in Indonesia’s economy, yet technological limitations often constrain productivity and competitiveness. D’Lor Bakery, located in Banyuwangi, previously relied on a conventional oven with limited capacity and uneven heat distribution, resulting in inconsistent product quality, high defect rates, and restricted production. To address these challenges, the Community Partnership Program (PKM) introduced a Gas Rotary Oven with automatic thermo control and gas leak detection. This innovation features a rotary rack system ensuring even heat distribution, a digital temperature control mechanism to stabilize baking conditions, and an MQ-5 sensor integrated with an automatic shut-off valve to enhance workplace safety. The implementation included design, training, and operational trials with a capacity of 56 trays per cycle. Results showed significant improvements: production capacity increased from 24 trays per cycle to 56 trays, with total output rising from 120 trays to 280 trays within five hours. Raw material processing also improved, from 10–15 kg of flour per cycle to 25–50 kg, while defective products decreased from 15–20% to 5–7%. Thermo control reduced temperature deviations by 15%, directly improving energy efficiency and lowering unit production costs. Economically, monthly revenue increased from IDR 4–5 million to IDR 8–12 million, with profit margins rising from 20% to 30%. Overall, the Gas Rotary Oven technology not only enhances productivity and consistency but also strengthens energy efficiency, product quality, and operational safety, making it a replicable solution for MSMEs in the bakery industry.